THE STORY OF "THE MAD MAN SEARCHING FOR TREASURE" FROM "LISON UT-TAYR" CHAPTER LXV [CHAPTER 65] - Jo`rayeva Dilovarxon (International Journal of Literature and Language Studies, 2026)
This article analyzes the content and essence of the story about a madman searching for treasure in the work of Lison ut-tayr, its mystical and moral ideas. The importance of teaching the story based on modern pedagogical approaches and its role in developing students' artistic thinking are highlighted.